How do different types of physical activity affect echocardiography findings and heart rate variability in children? - Ahmet Selman Guldagi; Ayhan Pektas; Mehmet Celegen; Mehmet Bilgehan Pektas (Medicine Science, 2022)
This study aims to investigate how different types of regular physical activity affect cardiac functions in school children. This is a cross-sectional review of 15 children who are not engaged with any regular physical activity (controls) and 60 athletes who swim (n=15), play basketball (n=15), play volleyball (n=15), and play tennis (n=15) regularly. The children who are not engaged with any sports, the children who swim, and the children who play basketball, volleyball and tennis are statistically similar with respect to age, sex, height, weight and body mass index (p>0.05 for all). When compared to the controls and other athletes, the swimmer children have significantly higher left ventricle diastolic mass, higher left ventricle posterior wall systolic thickness, lower mitral A wave, higher mitral annular plane systolic excursion and higher mitral E/A ratio (p=0.006, p=0.035, p=0.030, p=0.025 and p=0.043 respectively). The swimmer children have significantly lower interventricular septum E and A waves and significantly longer left ventricle IVRT than the controls and other athletes (p=0.001, p=0.040 and p=0.004 respectively). When compared with the controls and other athletes, the swimmer children have significantly lower p-wave dispersion and QT dispersion values (p=0.038 and p=0.035 respectively). The swimmer children have significantly higher total power and SDNN values than the controls and other athletes (p=0.046 and p=0.026 respectively). Swimming might contribute to the growth of cardiac muscles and help to improve the cardiac conduction system and enhance parasympathetic innervation of the heart in children. [Med-Science 2022; 11(4.000): 0-0]